Predicción estacional del clima en Centroamérica mediante la reducción de escala dinámica. Parte I: evaluación de los modelos de circulación general CCM3.6 y ECHAM 4.5 - Rivera, Erick R. (2008)
The ability of two general circulation models (ECHAM4.5 and CCM3.6) to simulate key climate features of Central America is determined by the evaluation of both precipitation and low-level wind fields for the period 1990-1999. According to the evaluation, ECHAM4.5 exhibits a more realistic representation of the regional climate. Therefore, its output is used in order to provide the initial and boundary conditions necessary to perform a dynamical downscaling using the regional model MM5v3.